Unplanned Post-Anesthesia Care Unit to ICU Transfer Following Cerebral Surgery: A Retrospective Study. Issue 1 (January 2023) - Cao, Qinqin; Fan, Chengjuan; Li, Wei; Bai, Shuling; Dong, Hemin; Meng, Haihong
Background: Unplanned transfer to intensive care unit (ICU) lead to reduced trust of patients and their families in medical staff and challenge medical staff to allocate scarce ICU resources. This study aimed to explore the incidence and risk factors of unplanned transfer to ICU during emergence from general anesthesia after cerebral surgery, and to provide guidelines for preventing unplanned transfer from post-anesthesia care unit (PACU) to ICU following cerebral surgery.Methods: This was a retrospective case-control study and included patients with unplanned transfer from PACU to ICU following cerebral surgery between January 2016 and December 2020. The control group comprised patients matched (2:1) for age (±5 years), sex, and operation date (±48 hours) as those in the case group. Stata14.0 was used for statistical analysis, and p < .05 indicated statistical significance.Results: A total of 11, 807 patients following cerebral surgery operations were cared in PACU during the study period. Of the 11, 807 operations, 81 unscheduled ICU transfer occurred (0.686%). Finally, 76 patients were included in the case group, and 152 in the control group. The following factors were identified as independent risk factors for unplanned ICU admission after neurosurgery: low mean blood oxygen (OR = 1.57, 95%CI: 1.20–2.04), low mean albumin (OR = 1.14, 95%CI: 1.03–1.25), slow mean heart rate (OR = 1.04, 95%CI: 1.00–1.08), blood transfusion (OR = 2.78, 95%CI: 1.02–7.58), emergency surgery (OR = 3.08, 95%CI: 1.07–8.87), lung disease (OR = 2.64, 95%CI: 1.06–6.60), and high mean blood glucose (OR = 1.71, 95%CI: 1.21–2.41).Conclusion: We identified independent risk factors for unplanned transfer from PACU to ICU after cerebral surgery based on electronic medical records. Early identification of patients who may undergo unplanned ICU transfer after cerebral surgery is important to provide guidance for accurately implementing a patient's level of care.